2017
DOI: 10.1523/jneurosci.2538-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Representation of Interaural Time Difference Is Impaired by Deafness in Development: Evidence from Children with Early Long-term Access to Sound through Bilateral Cochlear Implants Provided Simultaneously

Abstract: Accurate use of interaural time differences (ITDs) for spatial hearing may require access to bilateral auditory input during sensitive periods in human development. Providing bilateral cochlear implants (CIs) simultaneously promotes symmetrical development of bilateral auditory pathways but does not support normal ITD sensitivity. Thus, although binaural interactions are established by bilateral CIs in the auditory brainstem, potential deficits in cortical processing of ITDs remain. Cortical ITD processing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 83 publications
1
21
0
2
Order By: Relevance
“…5 , Fig. 6 ) which could support specialization of the right versus left auditory cortices ( Jiwani et al, 2016 ) and cortical integration of bilateral input ( Easwar et al, 2017b ). Second, bimodal hearing improves detection and understanding of speech in noise by providing access to sound from both sides of the head ( Arndt et al, 2015 , Arndt et al, 2017 , Ching et al, 2007 , Polonenko et al, 2015 , Thomas et al, 2017 ).…”
Section: Discussionmentioning
confidence: 74%
“…5 , Fig. 6 ) which could support specialization of the right versus left auditory cortices ( Jiwani et al, 2016 ) and cortical integration of bilateral input ( Easwar et al, 2017b ). Second, bimodal hearing improves detection and understanding of speech in noise by providing access to sound from both sides of the head ( Arndt et al, 2015 , Arndt et al, 2017 , Ching et al, 2007 , Polonenko et al, 2015 , Thomas et al, 2017 ).…”
Section: Discussionmentioning
confidence: 74%
“…Stimuli were presented at 50 dB above behavioral threshold (dB SL) and the order of click and tone‐burst presentation was counter balanced. As in previous studies (Easwar, Yamazaki, Deighton, Papsin, & Gordon, ), EEG responses from 62 cephalic electrodes referenced to the right earlobe were recorded using NeuroScan v4.5 with a Synamps‐II amplifier during passive listening (Compumedics USA, Inc., Charlotte, NC). Participants watched a silent subtitled movie, read a book, or played games on a tablet with minimal movement.…”
Section: Methodsmentioning
confidence: 99%
“…The spectral-temporal region refined by the low-frequency phonetic information from the additional HA might constitute useful glimpsing cues for the bimodal participants to fuse pieces of critical message as acoustic landmarks to 'bootstrap' lexical tone identification. In addition, from the perspective of neuroplasticity, bilateral bimodal hearing could prevent aural preference for the implanted ear and promote the cortical integration of input from bilateral auditory pathways [66,67]. Recently, Polonenko et al [67,68] demonstrated that children with asymmetric hearing loss, who received bimodal input with limited delay (i.e., restricting the duration of unilateral hearing), could reverse abnormal cortical aural preference and recover typical bilateral representations from both ears.…”
Section: Bimodal Benefits For Lexical Tone Recognitionmentioning
confidence: 99%